2018
DOI: 10.2741/4595
|View full text |Cite
|
Sign up to set email alerts
|

Uremic toxins are conditional danger- or homeostasis-associated molecular patterns

Abstract: We mined novel uremic toxin (UT) metabolomics/gene databases, and analyzed the expression changes of UT receptors and UT synthases in chronic kidney disease (CKD) and cardiovascular disease (CVD). We made the following observations: 1) UTs represent only 1/80th of human serum small-molecule metabolome; 2) Some UTs are increased in CKD and CVD; 3) UTs either induce or suppress the expression of inflammatory molecules; 4) The expression of UT genes is significantly modulated in CKD patients, and coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…We have previously reported that LPC could induce innate immune signatures in HAECs, resulting in prolonged EC activation [54]. To examine the hypothesis that IL-35 and IL-10 could block innate immune signatures in HAECs, we performed gene set enrichment analysis (GSEA) [55].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that LPC could induce innate immune signatures in HAECs, resulting in prolonged EC activation [54]. To examine the hypothesis that IL-35 and IL-10 could block innate immune signatures in HAECs, we performed gene set enrichment analysis (GSEA) [55].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, for the first time we propose a novel concept that DDCFs and DDRFs can act as nuclear sensors (Wang L. et al, 2016 ) for organelle stresses, which is a part of cellular sensor cross-talking network including classical DAMP receptors such as Toll-like receptors (Yang et al, 2008 ), caspase-1/Nod-like receptors and inflammasomes (Yin et al, 2013 ), conditional DAMPs receptors and our newly proposed homeostasis-associated molecular pattern receptors (Wang X. et al, 2016 ; Li et al, 2017a ; Wang et al, 2017 ; Sun et al, 2018 ), and mitochondrial ROS (Li et al, 2013 , 2016 , 2017b ; Cheng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that pro-atherogenic endogenous metabolites lysophospholipids such as lysophosphatidylcholines (lysoPC) act as conditional DAMPs. We previously proposed that lysoPC bind to their intrinsic receptors (conditional DAMP receptors) (Wang X. et al, 2016 ; Shao et al, 2017 ; Sun et al, 2018 ), and induce mitochondrial reactive oxygen species (mitoROS) (Li et al, 2013 , 2016 , 2017a ; Cheng et al, 2017 ) to upregulate aortic endothelial cell activation genes via histone 3 lysine 14 acetylation-AP1-dependent pathway (Li et al, 2018 ). However, it is not clear whether DDCFs and DDRFs act as the nuclear sensor for intracellular organelle stress, a part of our newly proposed cellular sensor cross-talking network.…”
Section: Introductionmentioning
confidence: 99%
“…Several UTs could potentially act as ligands in the activation of TLRs (Hauser et al, 2008). In this case, Sun et al (2018) reported that UTs can serve as conditional pro-inflammatory DAMPs (danger signal-associated molecular patterns) or anti-inflammatory HAMPs (homeostasisassociated molecular patterns) and modulate inflammation. Consequently, classical DAMP receptors signaling activation such as TLRs, NLR-inflammasome-activated caspase-1 and other pro-inflammatory cytokines can elevate uremic toxins levels, as well as be inhibited by CD4 + Foxp3 + regulatory T cells (Sun et al, 2018).…”
Section: Effect Of Uremic Toxins On the Immune Systemmentioning
confidence: 99%